Chronic Urticaria on Woman With Toxoplasmosis Post Spiramycin Treatment: A Rare Case - Putri, Astrid Amanda Wahyu; Prawira, Muhammad Edel Dwiputra; Mathilda, Harastha Qinthara; Rasyidi, Faradiani (Journal of Pakistan Association of Dermatologists, 2023)
Spiramycin is a macrolide antibiotic with a bacteriostatic action and is used as a toxoplasmosis treatment since the FDA considers it safe and can be taken throughout early pregnancy. As the therapeutic use of spiramycin increases, reports of hypersensitivity responses, characterized as urticaria, are also on the rise. A 27-year-old woman presented to the hospital with chief complaints of recurrent rash with redness and severe itch on her entire body for one week. The rash appeared after the patient was diagnosed with toxoplasmosis and instructed to take spiramycin regularly. Two months ago, the patient experienced the same complaints. The patient was diagnosed with spiramycin-induced chronic urticaria and administered dexamethasone, diphenhydramine, and fexofenadine orally. Clinical improvement is evident after three days of treatment, as evidenced by a weekly decrease in the UAS-7 score. Urticaria is a hypersensitivity reaction that can be triggered by antibiotic consumption. A comprehensive diagnosis is needed to determine the etiology of urticaria, including the history of drug consumption. Treatment of urticaria includes education and the administration of antihistamines and corticosteroids. Chronic urticaria requires special treatment from a dermato-venerologist.